G659 Evidence-based multidisciplinary assessment and management of children and adolescents with neurodevelopmental disorders. (May 2019) - Ogundele, MO; Ayyash, HF
Abstract : Background: Community Child Health (CCH) teams, including Neurodevelopmental Paediatricians, often deal with disorders such as ADHD, ASD and learning disability, which frequently present with emotional or behavioural difficulties. Emotional and Behavioural Disorders (EBD) in children are classified as internalizing or externalizing (Fig 1). They include challenging and aggressive behaviours, Disruptive behaviour disorders (Temper tantrums, ADHD, ODD, CD), emotional disorders (Anxiety, Depression, PTSD) and Autistic disorders (ASD, PDA, SCD). Taken as a whole these disorders affect up to 20.9% of children under 18. There is a complex relationship between EBD and Neurodevelopmental disorders (NDD) and significant overlap between the roles and skills of CCH and child Mental Health teams (Fig 2). Most young children with EBD first present to the CCH Paediatrician, who are increasingly expected to diagnose and treat these conditions. Methods: A literature review was conducted, including meta-analyses and national guidelines, searching Ovid, PubMed, PMC, CINAHL, EMBASE, Database of Abstracts and Reviews, and the Cochrane Database of Systematic reviews and other online sources. Results from audits of two local Child Developmental Centres are also presented. Results: Childhood NDD, behavioural and emotional difficulties (NDBED) have multi-factorial aetiologies where genes and environment interact multi-directionally. Many studies have identified a range of genetic and adverse environmental factors that interact to increase risk of developing any of these disorders. There is no single gold-standard diagnostic tool available for the diagnosis of NDEBDs, which largely depends on the clinical skills of an integrated multi-professional teams using reliable and validated assessment tools, combined with a high level of clinical experience and knowledge of differential diagnoses and effects of life experiences. Appropriate treatment strategies depend on careful assessment of the presenting problems in the context of family environment, socio-economic environment, the child's developmental level, temperament and physical health. It requires a multidisciplinary approach including various combinations of child- and family-focused psychological strategies including psycho-education, parenting skills training, CBT, behavioural modification and social communication enhancement techniques and appropriate social care and educational input. There are relevant roles for a wide range of professionals including Health Visitors, Nurses, Social workers, Educational specialists, Paediatricians, General practitioners (GP), Speech and language therapists (SALT), Neurologists, Psychiatrists, Psychologists, Support Workers, School Nurses, Neurophysiologists, Dentists, Clinical geneticists, Occupational therapists and Physiotherapists. Psychopharmacological treatment may be considered only in combination with psychological and other environmental interventions. Conclusion: Childhood EBD with their related NDD have significant negative impacts on children, families and society. They are associated with psychiatric co-morbidity and with poor academic, occupational, and psychosocial outcomes. It is important for professionals to be aware of the range of presentations, prevention and management strategies for these common disorders. Paediatric and psychiatric teams should thus be integrated and co-located to provide holistic diagnosis and management of children with NDD and EBD.